Evaluation of Bagworm, Metisa plana (Lepidoptera: Psychidae) Infestation and Beneficial Parasitoid in an Oil Palm Plantation, Perak, Malaysia - Thaer, Sarah; Abu Kassim, Faizah; Hasbullah, Nor Azlina; Al-Obaidi, Jameel R. (Journal of Science and Mathematics Letters, 2021)
Oil palm (Elaeis guineensis) planting is one of the economic pillars of countries rich in biodiversity in tropical regions. However, pest and disease are the most serious limitation of oil palm production. Bagworm, Metisa plana (Lepidoptera: Psychidae) is considered the most destructive pest in the oil palm plantation in Malaysia, which could cause high yield losses up to 43% over two years after a serious infestation and become a primary concern among stakeholders. Conventional excessive use of pesticides causes serious environmental pollutions and damage to non-target organisms. Thus, biological control can be reduced the pest populations safely and efficiently by beneficial insects such as parasitoids. This study aims to (i) evaluate the bagworm infestation in an oil palm plantation, Perak, Malaysia; (ii) determine the impact and damage of the bagworm stages on the oil palm plantation, and (iii) evaluate the parasitoid in such areas. A total of 57 palm trees have been systematically selected. Bagworm and parasitoid samples were collected in two stages at Felda Gunung Besout 2, Perak, Malaysia. Bagworm infestation severity was performed based on the severity scale of bagworm damage symptoms. The results showed that the incidence rates of oil palm trees are concerned 50.9%, 31.6%, 4%, 3.5% were low, moderate, high, and no incidence, respectively. Bagworm stages 1, 5, 6, and 7 are significantly impacted on the oil palm incidences and stage seven is the most impacted one; followed by stages 1, 6 and 5. Several parasitoids have been found; the highest one is Eulophidae: Tetrastichus s planipennisi.